Characterisation of grids of point detectors in maximum skin dose measurement in fluoroscopically-guided interventional procedures. Issue 8 (December 2015) - Dabin, J.; Negri, A.; Farah, J.; Ciraj-Bjelac, O.; Clairand, I.; De Angelis, C.; Domienik, J.; Jarvinen, H.; Kopec, R.; Majer, M.; Malchair, F.; Novák, L.; et al.
Highlights: The sampling uncertainty of point detectors in MSD measurement was investigated. Neuro and chemoembolisations, and percutaneous coronary interventions were studied. The measured MSD can be less than 50% of the actual MSD for certain procedures. Abstract: Purpose: Point detectors are frequently used to measure patient's maximum skin dose (MSD) in fluoroscopically-guided interventional procedures (IP). However, their performance and ability to detect the actual MSD are rarely evaluated. The present study investigates the sampling uncertainty associated with the use of grids of point detectors to measure MSD in IP. Method: Chemoembolisation of the liver (CE), percutaneous coronary intervention (PCI) and neuroembolisation (NE) procedures were studied. Spatial dose distributions were measured with XR-RV3 Gafchromic ® films for 176 procedures. These distributions were used to simulate measurements performed using grids of detectors such as thermoluminescence detectors, with detector spacing from 1.4 up to 10 cm. Results: The sampling uncertainty was the highest in PCI and NE procedures. With 40 detectors covering the film area (36 cm × 44 cm), the maximum dose would be on average 86% and 63% of the MSD measured with Gafchromic ® films in CE and PCI procedures, respectively. In NE procedures, with 27 detectors covering the film area (14 cm × 35 cm), the maximum dose measured would be on average 82% of the MSD obtained with the Gafchromic ® films. Conclusion: Thermoluminescence detectors show good energy and dose response in clinical beam qualities. However the poor spatial resolution of such point-like dosimeters may far outweigh their good dosimetric properties. The uncertainty from the sampling procedure should be estimated when point detectors are used in IP because it may lead to strong underestimation of the MSD.